Perancangan E-Commerce Penjualan Kue Dengan Menerapkan Model B2C (Business To Consumer) - Alda, Muhamad (PT. Delitekno Media Madiri, 2022)
Mumu Butikue Shop is one of the cake shops in Medan City. In carrying out the process of marketing and selling cakes, Toko Mumu Butikue still uses the traditional method. Customers have to come to the shop to select and buy the desired cake. By using this method, several problems still occur, including the very limited scope of the marketing process and the lack of customer interest in buying cakes at the Mumu Butikue Store. Customers need a lot of time, effort, and money to buy cakes. Because customers have to come directly to the store. The e-commerce that is built can process data for ordering cakes that are sold. This web-based e-commerce is built using the PHP programming language and MySQL database. As for the design process. E-Commerce, the author uses UML (Unified Modeling Language) tools consisting of Use Case Diagrams, Sequence Diagrams, Activity Diagrams, and Class Diagrams. The E-Commerce model used in this research is the B2C model. With the existence of E-Commerce, it is hoped that it will make it easier for the Mumu Butikue Shop to process sales data and expand the scope of marketing and cake sales.